A winter haunting - Simmons, Dan, 1948- (HarperTorch, 2003)
Returning to the small Illinois town of his childhood to pick up the pieces of his shattered life, and regain his confidence as a writer, Professor Dale Stewart leases an empty farmhouse of a long-dead friend, who had been murdered in the summer of 1960, but instead of finding peace and quiet, he finds that the house is haunted.